Cost management : - Hilton, RonalW. (Irwin/McGraw-Hill, 2006)
ilton/Maher/Selto (HMS) addresses traditional cost concepts, but makes cost accounting functional by focusing on measuring and managing costs. HMS maintains that, "Costs don’t just happen," and with a pro-active approach toward costs, accountants can add value to an organization. The real-world approach of this text, including the use of focus companies and the accompanying focus sites, provides a realistic business environment, and aids in student comprehension and interest in the subject.